KETERTARIKAN HAMA Sitophilus oryzae PADA BERAS, JAGUNG PIPILAN KACANG TANAH, KACANG KEDELAI, DAN KOPRA - Manueke, J.; Pelealu, Jantje (Universitas Sam Ratulangi, 2015)
ABSTRACT Â The purpose of research is to know the preferences of Sitophilus oryzae in rice, corn, peanut, soybeans, and copra. Experiments using observational and substitutional methods with research objeck is the interest of S. oryzae in some kind of postharvest material. Parameters measured were population density of pests, feeding damage caused by pests, and the relationship between population densty of pests and postharvest material damage caused by pests feed of S. oryzae. The results showed that S. oryzae choose food according to its main host. Population density are highest at 20.8 tail in rice, corn followed by14.0 tail, 8.2 tail in peanuts, 7,0 tail in soybeans and the lowest in copra is 4.0 tail. The results of feeding test showed that S. oryzae can not live in peanut, soybeans, and copra. Damage to feed straight to the population density S.oryzae. The amount of damage depends on the amount of feed that is higher pest populations, the greater damage in flicted on feed. Key words: preferences, Sitophylusoryzae, rice, corn, peanut, peanut soya, copra